THE EFFECT OF REGIME SUPERVISION, RISK APPETITE AND PROFILE ACTUARIAL ON FINANCIAL HEALTH LIFE INSURANCE COMPANY IN INDONESIA 2006-2018 - Putu Willy Adhitya Nugraha; Doddy Ariefianto (LPSDI Bina Patria, 2024)
Everyone must be able to do financial management. The importance of managing finances because no one does not know for sure to happen tomorrow. Life insurance is one of the financial instruments present in the financial industry as a place to invest and store funds in preparing for tomorrow. In choosing a company where funds are stored, people tend to look at the level of trust, one of which is financial health. In this study, researchers tried to raise the theme of Financial Health in life insurance companies which are influenced by three variables, namely risk appetite, regime supervision and actuarial profile. Researchers are trying to develop a Z-Score modification in banking to find out whether or not there is a connection between the three variables. The results showed that there was a significant influence of the regime supervision variable on financial health compared to other variables such as risk appetite and actuarial profile after conducting various tests. By the three tests, namely Linear Regression Analysis and Data Panel Estimation, the coefficient value still dominates more than 5%